Degree of satisfaction of users of a Dental Specialties Center in Paraíba (Research, Society and Development, 2020)
Aiming to evaluate the degree of user satisfaction in a Dental Speciality Center in Paraíba, a transversal analytical quantitative survey was realized. As an instrument of data collection, forms were applied to a sample of 144 users of the health service in the city of Patos-PB. In the study were analyzed the patients socio-demographic profile, accessibility and the solving of their oral problems. After the collection, the data was stored in a database and the analysis were developed using the Statistical Package for Social Sciences – SPSS for Windows, version 20 software and submitted in charts and tables. The main results showed that most users of the center are females (66.7%), aged 36 to 60 (36.8%), belonging to low-income families. The most sought specialities were endodontics (24.3%) and surgery (20.8%). Concerning the ease of access, 84% of the respondents affirmed that it was easy getting to the center. Of all the users interviewed, 93.1% which corresponds to 134 users, indicated that they were satisfied with the service offered while only 6.9% of research participants not present their problems solved. The analysis of the data allowed to conclude that the majority of the users are satisfied with the specialized services of this oral health unit, being the same recognized as resolving.